2005
DOI: 10.1890/03-0784
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Daphnia Phenotypes: A History of Industrial Pollution and Pelagic Ecosystem Response

Abstract: Phenotypic differences among species, even closely related species, may translate into distinct effects on ecosystem dynamics. In lakes, the generalist grazer genus Daphnia often has marked effects on the abundance of primary producers, the rate of primary production, and rates of nutrient cycling. The effects are particularly distinct during the clear-water phase (CWP) when algal biomass is driven to extremely low values as Daphnia densities undergo an annual population increase. Here we show that the timing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…However, the question remains whether the effects of rapid evolution on algalconsumer dynamics that we have documented here are important in nature. For example, are temporal changes in the densities of lake phytoplankton and zooplankton, such as the well-known clear-water phase dynamics observed in many tem-perate lakes (31,32), and the wide variation in algal food quality to grazers within and among lakes (33,34), influenced importantly by the level of algal genetic diversity available when acted upon by the natural selection imposed by grazers? (UTEX 26, 30, 265, 395, 396, 1803, 1809, 1911, and 2714).…”
Section: Discussionmentioning
confidence: 99%
“…However, the question remains whether the effects of rapid evolution on algalconsumer dynamics that we have documented here are important in nature. For example, are temporal changes in the densities of lake phytoplankton and zooplankton, such as the well-known clear-water phase dynamics observed in many tem-perate lakes (31,32), and the wide variation in algal food quality to grazers within and among lakes (33,34), influenced importantly by the level of algal genetic diversity available when acted upon by the natural selection imposed by grazers? (UTEX 26, 30, 265, 395, 396, 1803, 1809, 1911, and 2714).…”
Section: Discussionmentioning
confidence: 99%
“…Boronat et al (2001) demonstrated that cladoceran species have different halotolerances, ranging from fresh to saline water bodies, with D. longispina being estenohaline (range 0.5-1.2 g.L -1 ) and D. magna euryhaline (range 3.8-38 g.L -1 ). In fact, D. magna is one of the most halotolerant Daphnia species (Cowgill & Milazzo 1990, Rokneddine & Chentoufi 2004, Do Hong et al 2004, Hairston et al 2005. Tackx et al (2004) observed that cladocerans were mostly present in the freshwater part (<0.7 p.s.u.…”
Section: Discussionmentioning
confidence: 99%
“…(2) nia, in particular, is more or less tolerant to salinity and the differences among species can produce distinct effects in the system dynamics, such as in the abundance of primary producers, the rate of primary production and rates of nutrient cycling (Boronat et al 2001, Hairston et al 2005. As an example, euryhaline Daphnia magna lives in fresh, brackish and athalassohaline waters, while daphnids from the longispina group (D. longispina, D. galeata, D. cucullata) prefer waters with low mineralization and are very sensitive to magnesium, for example (e.g., concentrations above 0.6 g.L -1 become lethal for them) (Alonso 1996).…”
Section: Introductionmentioning
confidence: 99%
“…animal hairs Hodgson et al 1998, phytoliths Carnelli et al 2004, fish scales Davidson et al 2003), well-known proxies are being used in new ways, using newly developed analytical techniques and improved chronologies to estimate amounts and rates of change through time, and using new approaches to detect morphological or genetic changes in response to environmental change (e.g. Weider et al 1997;Kerfoot et al 1999;Cattaneo et al 2004;Hairston et al 2005). …”
Section: Future Directionsmentioning
confidence: 99%